Fresno's Human Services Coalition Luncheon Honoring Karen Humphrey - Watkins, Howard::::::::: (1985)
Karen Humphrey speaking at lectern; Supervisor Judy Andreen seated Karen Humphrey speaking at lectern; Supervisor Judy Andreen seated